The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/lno.10528
|View full text |Cite
|
Sign up to set email alerts
|

Export of terrigenous dissolved organic matter in a broad continental shelf

Abstract: Export of terrigenous dissolved organic matter (DOM) from rivers to the ocean plays an important role in the carbon cycle. Observations from six research cruises in 2014 were used to characterize the seasonal evolution of terrigenous DOM in the shallow and broad South Atlantic Bight (SAB) shelf. While DOM with a strong terrigenous molecular, optical and isotopic signature was restricted to a coastal band early in the year, a plume with terrigenous DOM extended further to the shelf break in late spring. The off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 74 publications
5
38
0
Order By: Relevance
“…The time series was not correlated with river discharge or with precipitation. The pattern revealed by the loading of PC 1, shown color coded in a van Krevelen diagram (Figure b), was different from the pattern typically observed in river to ocean transects (Medeiros, Babcock‐Adams, et al, ; Medeiros, Seidel, Dittmar, et al, ; Medeiros, Seidel, Gifford, et al, ; Medeiros, Seidel, Ward, et al, ; see also Figure d). This suggests that the mode was not related to the varying contribution of terrigenous vs marine sources to the estuarine DOM pool.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…The time series was not correlated with river discharge or with precipitation. The pattern revealed by the loading of PC 1, shown color coded in a van Krevelen diagram (Figure b), was different from the pattern typically observed in river to ocean transects (Medeiros, Babcock‐Adams, et al, ; Medeiros, Seidel, Dittmar, et al, ; Medeiros, Seidel, Gifford, et al, ; Medeiros, Seidel, Ward, et al, ; see also Figure d). This suggests that the mode was not related to the varying contribution of terrigenous vs marine sources to the estuarine DOM pool.…”
Section: Resultsmentioning
confidence: 65%
“…For the current sampling period, the total DOC export was larger at 108 Gg C/year. Medeiros, Babcock‐Adams, et al () showed that DOC flux is highly correlated to discharge at the Altamaha River. Thus, the 50% increase in DOC export compared to the long‐term average is likely related to increased river discharge during the study period associated with El Niño conditions (Sheldon & Burd, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The terrigenous content of DOM can be estimated from optical properties such as S 275–295 , based on its relationship with the terrigenous biomarker lignin, which has been employed as a proxy for such material in highly river‐influenced systems (Fichot and Benner ; Fichot et al ; Medeiros et al ). Assuming the previously identified S 275–295 ‐lignin relationships are valid for the Black Sea, S 275–295 values reported here suggest that Black Sea DOM is ∼ 4–12% terrigenous, having the lowest percentages at the surface and highest in the BBL, which is counterintuitive.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a midestuarine source of L 2 and HS Cu , which could be from increased fluxes of sedimentary organic carbon into the estuary, potentially partly linked to higher bioturbation by fiddler crabs and other invertebrates during summer. Published records show DOC concentrations range from around 3.0 to 9.0 mg/L along the estuary and are not conservative with salinity (Hodson, 2005;Medeiros et al, 2017). Like L 2 , the concentration of humic substances was generally highest in spring and generally constant from September to December, with elevated concentrations relative to salinity in August.…”
Section: Seasonality In the Datamentioning
confidence: 99%